Children of Uncertain Fortune : Mixed-Race Jamaicans in Britain and the Atlantic Family, 1733-1833 - Livesay, Daniel (Book collections on Project MUSE., 2018)
"By tracing the largely forgotten eighteenth-century migration of elite mixed-race individuals from Jamaica to Great Britain, "Children of Uncertain Fortune" reinterprets the evolution of British racial ideologies as a matter of negotiating family membership. Using wills, legal petitions, family correspondences, and inheritance lawsuits, Daniel Livesay ... follow[s] the hundreds of children born to white planters and Caribbean women of color who crossed the ocean for educational opportunities, professional apprenticeships, marriage prospects, or refuge from colonial prejudices"--